2019
DOI: 10.1101/848416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning of complex auditory patterns changes intrinsic and feedforward effective connectivity between Heschl’s gyrus and planum temporale

Abstract: Learning of complex auditory sequences such as language and music can be thought of as the continuous optimisation of internal predictive representations of sound-pattern regularities, driven by prediction errors. In predictive coding (PC), this occurs through changes in the intrinsic and extrinsic connectivity of the relevant cortical networks, whereby minimization of precision-weighted prediction error signals improves the accuracy of future predictions. Here, we employed Dynamic Causal Modelling (DCM) on fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
1
1
1
Order By: Relevance
“…That we found a reduction in top-down inhibition from secondary to primary auditory areas and a lack of modulation of forward connections contrasts with most previous studies in which both forward and backward connections show oddball-related effects (Auksztulewicz & Friston, 2015;Chennu et al, 2016;Garrido et al, 2007Garrido et al, , 2008Garrido, Kilner, Kiebel, et al, 2009;Lumaca et al, 2020;Schmidt et al, 2013). From a predictive coding perspective (Friston, 2005;Garrido, Kilner, Stephan, et al, 2009;Huang & Rao, 2011), forward and backward communication between brain areas reflects the update of predictive models by prediction error.…”
Section: Connectivity Patterns Underlying the Mmncontrasting
confidence: 99%
See 1 more Smart Citation
“…That we found a reduction in top-down inhibition from secondary to primary auditory areas and a lack of modulation of forward connections contrasts with most previous studies in which both forward and backward connections show oddball-related effects (Auksztulewicz & Friston, 2015;Chennu et al, 2016;Garrido et al, 2007Garrido et al, , 2008Garrido, Kilner, Kiebel, et al, 2009;Lumaca et al, 2020;Schmidt et al, 2013). From a predictive coding perspective (Friston, 2005;Garrido, Kilner, Stephan, et al, 2009;Huang & Rao, 2011), forward and backward communication between brain areas reflects the update of predictive models by prediction error.…”
Section: Connectivity Patterns Underlying the Mmncontrasting
confidence: 99%
“…Another finding that differs from previous research is the lack of involvement of frontal areas in the generation of the MMN, as indicated by the low probability of the opercular family. This is consistent with the lack of frontal generators previously reported for the same dataset (Quiroga-Martinez et al, 2019a) and in a recent fMRI study using simple musical stimuli (Lumaca et al, 2020). This suggests that the opercular peak found in the present sourcelevel statistical analyses may reflect source leakage.…”
Section: Connectivity Patterns Underlying the Mmnsupporting
confidence: 93%
“…As such, it is thought to index the activation of specialised automatic deviance detection networks (Kropotov et al, 1995;Bonetti et al, 2017Bonetti et al, , 2021cLumaca et al 2020). Studies consistently show heightened N1 amplitude in response to deviants, paralleling increased MMN in acoustic predictive processes (Näätänen, 2000;Inui et al, 2010).…”
Section: Introductionmentioning
confidence: 99%